Incidence of Typhoid and Paratyphoid Fevers Among Adolescents and Adults in Yangon, Myanmar. (7th March 2019) - Oo, Win Thandar; Myat, Tin Ohn; Htike, Wah Win; Ussher, James E; Murdoch, David R; Lwin, Kay Thi; Oo, Min Zaw; Maze, Michael J; Win, Hla Hla; Crump, John A
Abstract: Background: Accurate estimates of typhoid disease burden are needed to guide policy decisions, including on vaccine use. Data on the incidence of enteric fever in Myanmar are scarce. We estimated typhoid and paratyphoid fever incidence among adolescents and adults in Yangon, Myanmar, by combining sentinel hospital surveillance with a healthcare utilization survey. Methods: We conducted a population-based household health care utilization survey in the Yangon Region 12 March through 5 April 2018. Multipliers derived from this survey were then applied to hospital-based surveillance of Salmonella Typhi and Paratyphi A bloodstream infections from 5 October 2015 through 4 October 2016 at Yangon General Hospital (YGH) to estimate the incidence of typhoid and paratyphoid fevers among person ≥12 years of age. Results: A total of 336 households representing 1598 persons were enrolled in the health care utilization survey, and multipliers were derived based on responses to questions about healthcare seeking in the event of febrile illness. Of 671 Yangon residents enrolled over a 1-year period at YGH, we identified 33 (4.9%) with Salmonella Typhi and 9 (1.3%) with Salmonella Paratyphi A bloodstream infection. After applying multipliers, we estimated that the annual incidence of typhoid was 391 per 100 000 persons and paratyphoid was 107 per 100 000 persons. Conclusions: Enteric fever incidence is high in Yangon, Myanmar, warranting increased attention on prevention and control, including consideration of typhoid conjugate vaccine use as well as nonvaccine control measures. Research on incidence among infants and children, as well as sources and modes of transmission is needed.